Medical physics : exercises and examples - Worthoff, Wieland Alexander; Krojanski, Hans Georg; Suter, Dieter (De Gruyter textbook., 2014)
This textbook contains a comprehensive collection of exercises in medical physics with numerous illustrations - ideally suited for teaching and learning. Introductory sections summarize contents and learning targets of each chapter.